(untitled) (Eurasian Research Bulletin, 2022)
In this article discussed aspects of emotional impact in political discourse, their scope, and provides an analysis of English language materials. The influence of emotions on the listener and the listener in the process of political speech, the degree of emotionality in the speech of politicians, as well as their psychological impact are analyzed. In the article discussed the role and importance of emotional impact in convincing the addressee.